Peningkatan Hasil Belajar IPA Peserta Didik melalui Model Pembelajaran Picture and picture berbantuan Media Diorama di Sekolah Dasar - Aniatus Sholikhah; Sultan Majid Muhammad Salvara; Syailin Niclah Choirin Attatlina (Diniyah: Jurnal Pendidikan Dasar, 2022)
This study aims to describe the implementation of the picture and picture learning model assisted by diorama media in science subjects in elementary schools, to determine the increase in student activity by applying this learning model, and to determine the increase in student learning outcomes after learning is carried out. This research is classroom action research—data collection techniques in the form of observation and tests. The research data was then analyzed by descriptive qualitative. The results showed that applying the picture and picture learning model with the help of diorama media was carried out by following the learning syntax. Learning activities are getting better with the use of diorama media. During learning in each cycle, student activity gets better. Students look more active in class and do not hesitate to ask questions. Students learning outcomes increased after applying the picture and picture learning model assisted by diorama media. The number of students who achieved the KKM score (58) in the pre-cycle was only 4. However, after the implementation of the action, the number of students who achieved the KKM score increased to 9 students in cycle 1 and 18 students in cycle 2.Keywords: Learning outcomes, picture and picture learning models, the water cycle